Електрофізичні властивості системи поліамід–графенові нанопластини - Лісова, О.М.; Махно, С.М.; Гуня, Г.М.; Семенцов, Ю.І.; Картель, М.Т. (Наносистеми, наноматеріали, нанотехнології, 2017)
Досліджено властивості композитів на основі поліаміду 1212 з вмістом графенових нанопластин (ГН) до 0,06 об’ємної частки. ГН одержано методом електрохімічної дисперґації графітових електрод у лужному електроліті (KOH) низької концентрації при пропусканні струму від 6,0 до 60 мА/см². Розмір частинок — від 33 до 800 нм (найбільш ймовірний розмір — 41,6 нм); частинки утворювали стійку суспензію. Композити пресували з розтопу полімеру за температури у 460 К і тиску у 5 МПа. Методою ДТА показано, що збільшення вмісту ГН призводить до зміщення температури топлення полімеру в бік низьких температур і до підвищення деструкції полімеру. Концентраційні залежності електропровідности на низьких частотах і дійсної й уявної складових комплексної діелектричної проникности композитів на частоті у 9 ГГц нелінійно змінюються у концентраційному діяпазоні 0,005–0,03, що свідчить про наявність порогу протікання при вмісті ГН у 0,011. Для системи розраховано критичні індекси теорії перколяції. Методою імпедансної спектроскопії показано, що провідність вихідних ГН зумовлено переважно електронною складовою. Исследованы свойства композитов на основе полиамида 1212 с содержанием графеновых нанопластин (ГН) до 0,06 объёмной доли. ГН получены методом электрохимического диспергирования графитовых электродов в щелочном электролите (KOH) низкой концентрации при пропускании тока от 6,0 до 60 мА/см² . Размер частиц — от 33 до 800 нм (наиболее вероятный размер — 41,6 нм); частицы образовывали устойчивую суспензию. Композиты прессовали из расплава полимера при температуре 460 К и давлении 5 МПа. Методом ДТА показано, что увеличение содержания ГН приводит к смещению температуры плавления полимера в сторону низких температур и к повышению деструкции полимера. Концентрационные зависимости электропроводности на низких частотах и действительной ε' и мнимой ε'' составляющих комплексной диэлектрической проницаемости композитов на частоте 9 ГГц нелинейно изменяются в концентрационном диапазоне 0,005–0,03, что свидетельствует о наличии порога протекания при содержании ГН 0,011. Для системы рассчитаны критические индексы теории перколяции. Методом импедансной спектроскопии показано, что проводимость исходных ГН обусловлена преимущественно электронной составляющей. Graphene nanoplates (GN) are popular to research as their base or using them created many prototypes of a variety of electronic and optoelectronic devices, namely, LCD and solar cells, photodetectors, FETs, diodes, gas and biosensors of high sensitivity, capacitors of large capacity and so on. The properties of composites based on polyamide 1212 containing GN to 0.06 of volume fraction are studied. The GN are obtained by electrochemical dispersion of graphite electrodes in an alkaline electrolyte (KOH) of low concentration by passing a current of 6.0 to 60 mA/cm² . For separation of large graphite particles, nanoscale electrodes are placed between polypropylene filter fabric. Particle sizes are from 33 to 800 nm (most possible size is 41.6 nm). Particles form a stable suspension. Composites are obtained as follows: polyamide powder to industrial brand GN 1212 is added to the suspension, dispersed in ultrasonic disperser for 2 minutes, and dried at temperature of 350 K. The samples are pressed from polymer melt at temperature of 460 K and pressure of 5 MPa. DTA method shows that increasing content GN leads to a shift of the melting point of the polymer to low temperatures and to increased degradation of the polymer. Electrical conductivity at low frequencies are measured by twocontact method; the study of the real (ε') and imaginary (ε'') components of the complex permittivity of composites is held in a microwave range 8–12 GHz using electrodeless interferometer method. The concentration dependence of conductivity at low frequencies and the real and imaginary components of complex permittivity of composites at a frequency of 9 GHz are changing nonlinearly in the concentration range 0.005–0.03 that indicates the presence of percolation threshold, when the GN content is of 0.011. For the system designed, the critical percolation-theory index is estimated as t = 2.38, and the efficient array GN conductivity is σi = 1.3 6·10¹ Ohm⁻¹∙cm⁻¹. The method of impedance spectroscopy shows that the output GN conductance is due to electron component mainly.